The Relationship between the Concentration of Magnesium and the Presence of Depressive Symptoms and Selected Metabolic Disorders among Men over 50 Years of Age - Iwona Rotter; Adrian Wiatrak; Aleksandra Rył; Katarzyna Kotfis; Olimpia Sipak-Szmigiel; Magdalena Ptak; Natalia Tomska; Aleksandra Szylińska (Life, 2021)
Background: changes in the concentration of magnesium influence numerous processes in the body, such as hormone and lipid metabolism, nerve conduction, a number of biochemical pathways in the brain, and metabolic cycles. As a result, changes in magnesium concentration may contribute to the emergence of such pathologies as depressive and metabolic disorders, including hypertension, diabetes, and dyslipidemia. Methods: blood samples were taken from 342 men whose mean age was 61.66 ± 6.38 years. The concentrations of magnesium, lipid parameters, and glucose were determined using the spectrophotometric method. Anthropometric measurements were performed to determine each participant’s body mass index (BMI). Additionally, all participants completed two questionnaires: the Beck Depression Inventory and the author’s questionnaire. Results: abnormal levels of magnesium were found in 78 people. The analysis showed that these subjects more often suffered from metabolic disorders such as diabetes mellitus (p < 0.001), hypertension (p < 0.001), and depressive symptoms (p = 0.002) than participants with normal magnesium levels. Conclusion: our research showed that there is a relationship between abnormal levels of magnesium and the presence of self-reported conditions, such as diabetes, hypertension, and depressive symptoms among aging men. These findings may contribute to the improvement of the diagnosis and treatment of patients with these conditions.